How to limit the spillover from an inflation surge to inflation expectations - Lena Dräger; Michael Lamla; Damjan Pfajfar (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2022)
We study the effects of forward looking communication in an environment of rising inflation rates on German consumers' inflation expectations using a randomized control trial. We show that information about rising inflation increases short- and long-term inflation expectations. This initial increase in expectations can be mitigated using forward looking information about inflation. Among these information treatments, professional forecasters' projections seems to reduce inflation expectations by more than policymaker's characterization of inflation as a temporary phenomenon.
Keywords: E31; E52; E58; D84; 330; short-run and long-run inflation expectations; inflation surge; randomized control trial; survey experiment; persistent or transitory inflation shock